A MODIFIED GAUSSIAN FUNCTION FOR MODELING MAGNETIC HYSTERESIS UNDER DYNAMIC CONDITIONS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents a novel modified Gaussian distribution for the Preisach model to improve magnetic hysteresis modeling. Unlike classical distributions, the proposed approach incorporates additional parameters that provide a more accurate representation of the dispersion of elementary relay switching thresholds. The influence of each parameter on the hysteresis loop shape is analyzed in detail. The model parameters are identified using the particle swarm optimization (PSO) method, based on experimental data. The simulation results are then compared with experimental measurements on a NiFe₂O₄ ferrite, accounting for dynamic effects due to temperature and frequency. The results show that the proposed model provides good agreement between simulation and experiment, particularly regarding the width and slope of the hysteresis loops.
Keywords: Preisach model; Magnetic hysteresis; Modified Gaussian distribution; Particle swarm optimization (PSO); NiFe₂O₄; Dynamic effects; Frequency; Temperature